Combining lipidomics and efficacy‐oriented compatibility revealed that Qi Ge decoction compatibility improved lipid metabolism in hyperlipidemic rats. (16th February 2023) - Fan, Simin; Yu, Xiaoqing; Li, Yanfang; Zhou, Zunming; Ye, Jintong; Guo, Kaixin; Huang, Keer; Ke, Xuehong
Abstract: The mechanism underlying traditional Chinese medicine (TCM) compatibility is difficult to understand. This study combined lipidomics and efficacy‐oriented compatibility to explore underlying compatibility mechanisms of Qi Ge decoction (QG) for improving lipid metabolism in hyperlipidemic rats. The QG was divided into three groups according to the efficacy group strategy: the Huangqi–Gegen (HG), Chenpi (CP), and QG groups. Hyperlipidemic rats were treated with QG, HG, CP, or atorvastatin for 3 weeks. The mass spectral data of widely targeted lipidomics were used to evaluate lipid changes. Principal component analysis and orthogonal partial least squares discriminant analysis were used to assess the lipidomic differences between the groups. MetaboAnalyst 5.0 was used to explore metabolic pathways. Compared with the model group, serum cholesterol, triglyceride, and hepatic steatosis were significantly reduced by QG, whereas HG and CP had no significant effects on these indexes. Lipidomics showed that QG, HG, and CP back‐regulated 60, 11, and 14 lipids, respectively. Compared with HG and CP, QG had more metabolic targets in diglycerides, triglycerides, ceramides, and phosphatidylethanolamines. Pathway analysis indicated that QG mainly regulated glycerophospholipid and glycerolipid metabolism. This study provided a new method of combining lipidomics and efficacy‐oriented compatibility for exploring the scientific connotation of TCM compatibility.